Pengaruh Literasi Keuangan Syariah Dan Perilaku Kewirausahaan Muslim Terhadap Kinerja Pelaku Usaha Di Malang Raya - Anggraeni, Dwi Adela; Mardani, Ronny Malavia; Dianawati, Eris (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine and analyze the relationship between Islamic Financial Literacy and Muslim Entrepreneurial Behavior on the Performance of Business Actors. This research uses studies on Business Actors in Malang, both in the City and Regency. Data was obtained by distributing questionnaires to business actors selected using purposive sampling. Determining the number of samples using the Slovin formula and the results obtained were 72 respondents. The analytical method used in this research was the research instrument test (Validity Test, Reliability Test), Normality Test. Classic assumption test (Multicolinearity Test, Heteroskedasticity Test). Multiple linear regression analysis. Hypothesis test (F test, t test) and Coefficient of Determination Test using SPSS data processing. The results of this research show that Islamic Financial Literacy does not influence the Performance of Business Actors. Muslim Entrepreneurial Behavior has a significantly positive effect on the Performance of Business Actors. Keywords:Islamic Financial Literacy, Muslim Entrepreneurial Behavior, and Business Actor Performance